Conservative Management of a Maxillary Lateral Incisor with an Apical Third Root Perforation: A Case Report - Damayanti, Nurul Astrina; Fuddjiantari, Dian Natalina; Untara, Tri Endra; Kristanti, Yulita (Journal of Dentistry Indonesia, 2020)
Perforation is one of iatrogenic factors responsible for endodontic failure. Root canal perforation can occur at the cervical, mid-root, or apical levels. Non-surgical (conservative) perforation repair offers less tissue destruction and easy isolation during treatment. Objective: To explain the management of apical third root perforation using the conservative technique. Case Report: This case report describes a 29-year-old patient who came for management of right maxillary lateral incisor with apical third root perforation on the labial aspect. The location of apical third root perforation was evaluated using cone beam computed tomography (CBCT). Root perforation was sealed using mineral trioxide aggregate (MTA). MTA was applied in conservative technique with hand filling. MTA was dispensed into the original canal while maintaining the patency of the perforated canal, followed by dispensed of MTA into the perforated canal. Conclusion: Root perforation should be identified as soon as possible and could be easily examined using CBCT. Non-surgical root perforation treatment is recommended in intact periodontal attachment and in absence of inherent complication. Repairing the root perforation promote the proper healing of the periapical tissue and increase the success rate of retreatment.